Hubungan Perilaku Cuci Tangan Pakai Sabun dengan Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Tanjung Pati Kabupaten Lima Puluh Kota - Finta Aldian Wahyuni; Lindawati; Sugriarta, Evino (CV. CENDIKIA JENIUS INDONESIA, 2024)
People's clean living behavior is one of the risk factors that can influence health status. One form of implementing clean living behavior is washing hands with soap (CTPS). One of the risks of poor CTPS behavior is that it causes diarrhea, especially in children under five. The highest prevalence of diarrhea among children under five is in Limapuluh Kota Regency, namely in the Tanjung Pati Community Health Center working area, at 23.8%. The aim of this research was to determine the relationship between CTPS behavior and the incidence of diarrhea in toddlers in the working area of ​​the Tanjung Pati Community Health Center, Limapuluh Kota Regency. This research is an observational study. The sample in this study was 16 toddlers (cases) and 16 control toddlers). This research was conducted from August to December 2023 by means of interviews and observations. Data analysis used the chi-square test. The research results showed that in the case group there were 68.8% of respondents with poor CTPS behavior who suffered from diarrhea, while 31.2% of respondents with good CTPS behavior suffered from diarrhea. The results of the chi-square statistical test showed a p value of 0.004 (p ≤ 0.05). Conclusion: there is a relationship between hand washing behavior with soap and the incidence of diarrhea in toddlers. It is recommended that health workers be able to change mindsets, thought patterns, ways of thinking and feelings regarding the behavior of washing hands with soap.